The Effects of Operating Income, Gross Profit, Net Income, and Total Accruals on Future Cash Flows: Empirical Evidence from Mining Sector Companies Listed on The Indonesia Stock Exchange, 2020–2024 - Anisa Fitriani; Irfan Gaffar Adnan; Melvin Rahma Sayuga Subroto (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the effects of operating income, gross profit, net income, and total accruals on future cash flows among mining-sector companies listed on the Indonesia Stock Exchange during 2020–2024. A quantitative approach was employed using secondary data obtained from audited annual financial statements. Purposive sampling yielded 10 companies and 50 balanced panel observations. The data were analyzed through panel-data regression in EViews. The Chow and Hausman tests supported the Fixed Effect Model, and Generalized Least Squares with cross-section weights was subsequently applied to address heteroskedasticity. The results show that operating income has a negative and significant effect on future cash flows, although this coefficient should be interpreted cautiously because of the high correlations among the earnings components. Gross profit has no significant effect. Net income has a positive and significant effect and emerges as the most reliable earnings component for predicting future cash flows. Total accruals have a negative and significant effect, indicating that a larger accrual component in reported earnings is associated with lower cash realization in the subsequent period. Collectively, operating income, gross profit, net income, and total accruals significantly affect future cash flows. The adjusted R-squared of 0.845 indicates that the model explains 84.5% of the variation in future cash flows. These findings underscore the importance of net income and total accruals for investors, creditors, and management when assessing the liquidity prospects of mining companies